2020
DOI: 10.1002/jmv.26223
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcomes of four HIV patients with COVID‐19 in Wuhan, China

Abstract: Serial chest computed tomography scans of four patients since symptom onset. (1) Patient A: (A and D) diffuse bilateral groundglass opacities (GGOs) predominantly involving perihilar and midzones with relative subpleural sparing at 3 weeks after symptom onset. (B and E) A mixed pattern of GGOs, reticulation and air space consolidation, cystic airspaces, decreased lung volume, and compensatory increased anteriorposterior chest diameter at 9 weeks. (C and F) Partial resolution of various lesions at 12 weeks. (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
1
14
1
Order By: Relevance
“…As a matter of fact, patients with a fatal outcome presented with lower CD4 counts, even if the difference was not statistically significant when analyzed according to a multivariate model. These findings confirm previously reported observations 6,15 …”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…As a matter of fact, patients with a fatal outcome presented with lower CD4 counts, even if the difference was not statistically significant when analyzed according to a multivariate model. These findings confirm previously reported observations 6,15 …”
Section: Discussionsupporting
confidence: 94%
“…Most previous studies in PLWHIV concentrated on patients admitted to the hospital because of COVID‐19 6,8,15 . In our cohort, most of the included patients were not admitted to the hospital, testifying that, even in HIV‐positive subjects, SARS‐CoV‐2 may present as a mild diseases not requiring hospital admission or intensive care 16,17 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Maggiolo compared 55 cases of SARS-CoV-2 infection with 69 asymptomatic people living with HIV (PLHIV) negative for SARS-CoV-2 RT-PCR and/or serology, and suggested that HIVpositive individuals are not protected from SARS-CoV-2 infection or have a lower risk of severe disease and those with low CD4 + T cell counts might have worse outcomes [15]. Studies also suggested that HIV-positive individuals should not be considered to be protected from SARS-CoV-2 infection or to have lower risk of severe disease [16,17].…”
Section: Discussionmentioning
confidence: 99%